2005
DOI: 10.1007/s10531-004-0316-9
|View full text |Cite
|
Sign up to set email alerts
|

Conserving the Sacred Medicine Mountains: A Vegetation Analysis of Tibetan Sacred Sites in Northwest Yunnan

Abstract: Mount Kawa Karpo of the Menri ('Medicine Mountains' in Tibetan), in the eastern Himalayas, is one of the most sacred mountains to Tibetan Buddhists. Numerous sacred sites are found between 1900 and 4000 m, and at higher elevations the area as a whole is considered a sacred landscape. Religious beliefs may affect the ecology of these sacred areas, resulting in unique ecological characteristics of importance to conservation; recent studies have demonstrated that sacred areas can often play a major role in conser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(72 citation statements)
references
References 13 publications
0
72
0
Order By: Relevance
“…Tibetan sacred sites, as a form of Community Conserved Area (CCAs; Oviedo 2006, Smyth 2006, have been effectively protected by local people and function to protect threatened species, biodiversity, and ecosystem services (Anderson et al 2005, Zou et al 2005, Salick et al 2007, Xiang et al 2008. In terms of access and utilization, Tibetan sacred sites were comparable to several IUCN protected area categories (IUCN 1994): Forbidden areas and sacred lakes with strict prohibitions are analogous to Category I (Strict nature reserve and wilderness areas); sacred mountains could be allocated into Categories II (National park), V (Protected landscape), or VI (Managed resource protected area), depending on how strictly the traditional regulations are executed; and monasteries and sacred relics are consistent with the definition of Category III (Natural monument).…”
Section: Tibetan Sacred Sites Serve As a Landscape-level Conservationmentioning
confidence: 99%
See 2 more Smart Citations
“…Tibetan sacred sites, as a form of Community Conserved Area (CCAs; Oviedo 2006, Smyth 2006, have been effectively protected by local people and function to protect threatened species, biodiversity, and ecosystem services (Anderson et al 2005, Zou et al 2005, Salick et al 2007, Xiang et al 2008. In terms of access and utilization, Tibetan sacred sites were comparable to several IUCN protected area categories (IUCN 1994): Forbidden areas and sacred lakes with strict prohibitions are analogous to Category I (Strict nature reserve and wilderness areas); sacred mountains could be allocated into Categories II (National park), V (Protected landscape), or VI (Managed resource protected area), depending on how strictly the traditional regulations are executed; and monasteries and sacred relics are consistent with the definition of Category III (Natural monument).…”
Section: Tibetan Sacred Sites Serve As a Landscape-level Conservationmentioning
confidence: 99%
“…The significance of Tibetan sacred sites in conservation centers on their widespread distribution (Xu et al 2005, Shen et al 2007) and their function in conserving both mature forest (Zou et al 2005, Salick et al 2007, Xiang et al 2008) and threatened species (Anderson et al 2005). Nevertheless, our knowledge on the spatial distribution and management of Tibetan sacred sites is still poor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This confluence of ecotypes results in extraordinary biodiversity in mountain region is one of the global hotspots [62,63], examined the relationships among sacred sites, elevation and vegetation with Geographical Information Systems (GIS) and indicated that sacred sites are found to have more species and diverse habitats than randomly selected non-sacred sites. and every branch that beareth fruit, he purgeth it, that it may bring forth more fruit….…”
Section: Sacred Grove In Mountain Conservationmentioning
confidence: 99%
“…While research has been conducted covering the ecology and botanical strengths of Tibetan regions [15,[21][22][23][24][25][26][27][28][29], it is important to study more deeply into the pharmaceutical potentials of such materials. A large amount of research is centered around finding active constituents within specific Tibetan medical ingredients [30][31][32][33][34][35][36][37][38][39][40][41].…”
Section: Future Developmentsmentioning
confidence: 99%